Hydrophilic Linkers and Polar Contacts Affect Aggregation of FG Repeat Peptides - Dölker, Nicole (The Biophysical Society, 2010)
Transport of large proteins into the nucleus involves two events, binding of the cargo protein to a transport receptor in the cytoplasm and passage of the cargo-transporter complex through the selective permeability barrier of the nuclear pore complex. The permeability barrier is formed by largely disordered polypeptides, each containing a number of conserved hydrophobic phenylalanine-glycine (FG) sequence motifs, connected by hydrophilic linkers of varying sequence (FG nups). How the motifs interact to form the permeability barrier, however, is not yet known. We have, therefore, carried out molecular dynamics simulations on various model FG repeat peptides to study the aggregation propensity of FG nups and the specific roles of the hydrophobic FG motifs and the hydrophilic linkers. Our simulations show spontaneous aggregation of the model nups into hydrated aggregates, which exhibit structural features assumed to be part of the permeability barrier. Our simulations suggest that short β-sheets are an important structural feature of the aggregates and that Phe residues are sufficiently exposed to allow rapid binding of transport receptors. A surprisingly large influence of the amino acid composition of the hydrophilic linkers on aggregation is seen, as well as a major contribution of hydrogen-bonding patterns.